An overview of interactive language activities in learning Arabic among secondary school students via Frog Virtual Learning Environment (VLE) - Mohamad Mokhtar, Nur Najihah; Md Ghalib, Mohd. Feham (Kulliyyah of Languages and Management (KLM), International Islamic University Malaysia (IIUM), 2016)
The use of Frog VLE has become increasingly common among students in Malaysia and it is the most advanced learning platform that has been introduced by the Ministry of Education in upgrading the education system based on the Malaysian Education Blueprint 2013-2025 (Hiong & Umbit, 2014). This paper focuses on promoting the use of interactive language activities in Frog VLE as a tool in learning Arabic language among students, in order to introduce them to effective ways of learning foreign language as well as to increase their motivation in learning. Although the implementation of Frog VLE has been made for quite some time, its practice in teaching and learning Arabic Language course is still lacking. The current study will investigate the modules in Frog VLE that match language activities. Some modules which are preferable to users will be presented and discussed. Hopefully, this can give some light in the implementation of Frog VLE in teaching and learning Arabic language.